The Effectiveness of Story Mapping to Teach Reading to the First Semester of English Department Students at STKIP PGRI Tulungagung - Dina Kartikawati (STKIP PGRI Tulungagung, 2018)
Reading ability is a wonderful ability which is only had by human. The writer can communicate with many people around the world through script. Problems appear when the students must read and comprehend the text of foreign language. It is also faced by students majoring in English education. They are also be accused to be able to teach reading to their future students.To test whether they understand the text they have read or not is by giving them some questions. The question may ask about the main idea or about the details of the text. From the collected data, most students from many grades are still get difficulty in comprehending the text.The statement of the problem of this study is â€œIs story mapping effective to teach reading to English department students at STKIP PGRI Tulungagung?â€ The objective of this study is to know whether story mapping effective to teach reading to English department students at STKIP PGRI Tulungagung. The design of this study is quasi experimental design, with one group pre-test and post-test design.The population of this study is students of reading 1 class. It consists of 52 students. This study uses 23 students as sample. The sampling of this study is simple random sampling. The technique of collecting is pre-test, which provides a measure on some attribute or characteristics that you assess for participant in an experimentalbefore they receive a treatment, treatment by using story mapping, and post-test, which is conducted after conducting the teaching through story mapping. The data of experimental research is analyzed by t-test formula. The hypotheses of this study are story mapping is not effective to teach reading to English department students at STKIP PGRI Tulungagung (H0) and story mapping is effective to teach reading to English department students at STKIP PGRI Tulungagung (Ha). After the researcher conducted the research, the researcher concludes that the studentâ€™s competence in reading ability before treatment was poor because the mean of the total score of 23 students was only 55.43. The studentâ€™s competence in reading ability after treatment is better than before given treatment because the mean of the total score of 23 students wasÂ 71.30. Based on the statistical using SPSS 16.0 shows that the significant value was 0.000 while significant level, the alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected.